Delayed Credit Recovery in Croatia: Supply or Demand Driven? - Mirna Dumičić; Igor Ljubaj (Journal of Central Banking Theory and Practice, 2018)
In order to enhance the understanding of credit cycle dynamics in Croatia, we explore the evolution of credit demand and credit supply of corporates and households in Croatia and identify their determinants based on the switching regression framework. These results are crosschecked by the insights from the bank lending survey. The conducted analysis shows there are both supply and demand-side factors that limit the possibility of intensifying household and corporate credit activity. However, a more pronounced drag seems to be coming from subdued demand, which is greatly influenced by the unfavourable domestic macroeconomic environment and, particularly, GDP developments. This suggests that it is not unusual that credit recovery is still missing but also confirms that the scope for monetary policy to stimulate lending is limited.
Keywords: E44; G21; G28; 330; credit supply; credit demand; households; corporates; Croatia; switching regression framework.